2022
DOI: 10.1111/1749-4877.12682
|View full text |Cite
|
Sign up to set email alerts
|

Safety is increasingly important in cobweb spiders based on life history

Abstract: Detritus‐based, bell‐shaped cobwebs are an ideal model to research the plasticity of web architecture due to clearly separate defense and foraging components. We performed a thorough field investigation on the web architectures of Campanicola campanulata to research its cobweb architecture variation during the growth process and analyzed the energy trade‐offs between foraging and defense at different developmental stages. The results indicated that as female C. campanulata grew, they dedicated more energy to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Most euryphagous spiders seem to avoid preying on ants because they have strong spines, mandibles, and formic acid for effective group attacks (Pekaŕ and Toft, 2015). Our results are consistent with previous studies showing that egg production has significant effects on cobweb (black widow web) architecture (Dirienzo and Aonuma, 2018;Zhang et al, 2022a).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Most euryphagous spiders seem to avoid preying on ants because they have strong spines, mandibles, and formic acid for effective group attacks (Pekaŕ and Toft, 2015). Our results are consistent with previous studies showing that egg production has significant effects on cobweb (black widow web) architecture (Dirienzo and Aonuma, 2018;Zhang et al, 2022a).…”
Section: Discussionsupporting
confidence: 91%
“…The behavior of cobweb-building spiders that build detritus-based, bell-shaped cobweb has attracted the attention of researchers in recent years (Li et al, 2021). Previous studies have shown that the spider's behavior is highly plastic and susceptible to internal factors such as development stage and feeding (Zhang et al, 2022a;Zhang et al, 2022b). However, whether external factors such as prey or predator cues and detritus material weight will affect the cobweb-building behavior of those spiders is still unknown.…”
Section: Open Accessmentioning
confidence: 99%
See 3 more Smart Citations